Первые товарищи: [повесть] / Лилия Чарская ; [художник А. Кузьмин] - Чарская Лидия Алексеевна (Мировая книжка, 2012)
Экземпляры: ООД, №4, №6, №9, №14, №15 (20160404) / Инвентарный номер: 36695 / Цена: 198.00 / Авт.знак: Ч-22 / ББК: 84(2Рос=Рус)1